Studying the use cases of Vision AI in detecting QR Code Phishing - Pradhan, Shalabh (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
This paper dives into the current widespread use of QR codes in our everyday lives. QR codes have been instrumental in disseminating information in the digital age and more so in the mobile era. There are multiple use cases ranging from sharing the Local Wifi to making digital payments. As such QR Codes are short, easy to add and convenient way to collect payments, share feedback or make your favorite music player , play music. This has also lead to multiple attack paths  and has created a cybersecurity attack vector that is difficult to catch and has potential to cause disruption in our current techno-business stack. On the other hand, the exponential rise of AI use cases to solve complex problems (including its use cases in Cybersecurity domain) has been impressive. In this study we will take a closer look at QR Codes, their use cases and potential attack vectors. We will then document the use cases to use Vision AI to prevent QR code attacks especially those that are phishing related attacks.